An atypical case of a pulmonary mass in an immunocompromised patient. Issue 5 (2nd September 2020) - Cardinaels, Nina; Van Rompaey, Winand; Bos, Saskia; Bode, Hannelore; Tousseyn, Thomas; Van Bleyenbergh, Pascal
ABSTRACT: Objectives: Pulmonary lymphomatoid granulomatosis (PLG) is a rare angiocentric and angiodestructive EBV-associated lymphoproliferative disorder which almost always affects the lungs. PLG is more commonly diagnosed in patients with immunodeficiency and is associated with Epstein-Barr virus (EBV). 'Drug induced PLG' or 'iatrogenic immunodeficiency-associated lymphoproliferative disorder' is a special form of PLG described in patient with inflammatory bowel diseases treated with Azathioprine. Methods: We report a case of drug-induced PLG in a 68-year-old patient with Crohn's disease presenting with pain at the right hemithorax, fatigue and shortness of breath with a pulmonary mass. Results: Although initial diagnostic findings were misleading, an open lung biopsy eventually led to the diagnosis of drug-induced PLG. Conclusion: The diagnosis of PLG is challenging because the disease is rare and the histological features can be very subtle. Correct diagnosis relies on histopathology and immunohistochemical staining and EBV RNA in situ hybridization with sampling of large and different amounts of pathologic tissue in the hands of expert pathologists. In drug-induced PLG specifically, withdrawal of the immunosuppressive agent can lead to disease regression.